A Skinning Method in Real-time Skeletal Character Animation - Xu, Tianchen; Chen, Mo; Xie, Ming; Wu, Enhua (International Journal of Virtual Reality, 2011)
With regard to skeletal character animation, the question on how to ensure the quality of transition between key frames is of crucial importance. The lack of properly defined motion ranges based on movements would leave the animator with no choice but intervene the result based on camera perspective afterwards, thus creating a lot more work for the animator to modify or clean up the animation curves. Although a number of methods have been raised in these years, such as the Linear Blending Skinning (LBS), they may still have shortcomings in some specific cases, one of which is the obvious unnatural deformation around the joint areas. The primary investigation in this paper is directed to address the problem and improve the framework of rendering in real-time environment with satisfactory skinning effect to the aforementioned scenario, with assistance of GPU computation